Value transformations of youth at the intersection of traditional values and global influences (The Journal of Psychology and Sociology, 2025)
The article analyzes the value orientations of Kazakhstani youth within the interplay of globalization and glocalization. Young people rapidly adopt new social norms while remaining shaped by a traditional cultural code, making their values a sensitive indicator of social transformation.The study employs a quantitative methodology using a survey approach. The findings reveal an increasing aspiration for autonomy, educational mobility, and self-development, combined with a relatively low reliance on traditions and the advice of elders. Weak social trust emerges as a significant constraint limiting the accumulation of social capital and collective engagement.Overall, youth value orientations display a distinctly hybrid character: instead of rejecting traditional norms, young people integrate global influences and adopt a pragmatic, future-oriented outlook.The results provide an applied basis for educational policy, gender equality programs, and migration strategies, reflecting the ongoing transformation of youth identity in contemporary Kazakhstan.Keywords: traditional values, global influences, intersection, youth, transformation.